Winter as a Source of Economic Growth - Mayarenkov, Sergey (project baikal, 2020)
The article considers the potential of the territories located in a cold climate zone. The author outlines the issues that can become a “growing point” for such territories, as well as the direction of theoretical studies for implementation of practical measures. The investment attractiveness of “winter” cities and Irkutsk in particular is highlighted.
Keywords: Irkutsk; project “Winter City”; “summer” city; economic growth; climate resources; strategic initiatives